"I Get My Therapy From Work": Wellness Recovery Action Plan Strategies That Support Employment Success. (April 2017) - Olney, Marjorie F.; Emery-Flores, Deborah S.
Although the Wellness Recovery Action Plan (WRAP) has been studied in the context of recovery from mental illness, peer-led services, effectiveness, and improving self-advocacy skills of clients, the relationship between employment success and WRAP has not yet been examined. The objective of the study was to explore the impact of WRAP on employment and how individuals with psychiatric disabilities utilized WRAP strategies for employment success. Ten working-age individuals who completed WRAP training and subsequently worked for at least 90 days engaged in semi-structured interviews about their experiences with WRAP and employment. Transcripts of the interviews were analyzed and three themes emerged from the study: (a) Then and Now, (b) Strategies for Wellness, and (c) Toward Employment Success. Findings showed that WRAP strategies facilitated success in employment and that employment was an important component of recovery from mental illness.